Fluorescence induction in Pine. Response of Pinus halepensis Miller, P. nigra Arnold and P. pinaster Aiton to hexazinone and simazine herbicides - Villarroya, M.; Ortega, M.; Chueca, M. C.; García Baudín, J. M. (Forest Systems, 2001)
The first phases of the development of pines could be affected by weed competition. The use of herbicides is fundamental for weed control but herbicide treatment must be safe for pines. This work study the effect of two herbicides, hexazinone and simazine, over three pine species Pinus halepensis, P. nigra and P. pinaster by means of measures of the fast phase of the chlorophyll fluorescence induction kinetics. The study is conducted in early caulinars leaves of pine treated for 48 hours with doses of 2 and 4 ppm of each herbicide. Herbicide treatment and recovery of plants was done under hydroponics conditions in climatic chamber. P. nigra was more tolerant than P. pinaster and P. halepensis to hexazinone. There were no differences between species in simazine response. The three pine species show better recovery of photosynthetic activity in hexazinone treatments than in simazine treatments, indicating better tolerance of tree to hexazinone than to simazine.